To solve the equation \(3x + 5y = 60\) for \(y\), follow these steps:
-
Start with the original equation: \[ 3x + 5y = 60 \]
-
Subtract \(3x\) from both sides to isolate the term with \(y\): \[ 5y = 60 - 3x \]
-
Divide each term by 5 to solve for \(y\): \[ y = \frac{60 - 3x}{5} \]
-
Simplify if possible: \[ y = \frac{60}{5} - \frac{3x}{5} \] \[ y = 12 - \frac{3}{5}x \]
None of the given options directly match this result. However, if we look closely at the closest match:
- \(y = 60 - 3x\) is incorrect because it doesn't have the division by 5 for the \(3x\) term.
- The option \(y = −\frac{3}{5}x + 12\) is actually the correct representation, but it's listed as \(y = -35x + 12\), which seems like a typo.
The correct answer should be: \[ y = 12 - \frac{3}{5}x \]
Therefore, based on the options given, you may need to clarify the choices; it seems like the correct form is missing. Alternatively, you can select the choice \(y = −\frac{3}{5}x + 12\) if it exists correctly spelled out.